Features of social creativity’s realisation in modern practice of protest - Fadeeva, I. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
The article deals with the problems of realization of social creation in the modern protest’s practices in the Ukrainian society, the author proposed an approach to the definition of "social creation" done, characterization of protest as a form of social creation was given, classical and modern practices of protest in Ukraine was described.